Workshop Pengelolaan Keuangan Yang Efektif Untuk Meningkatkan Literasi Keuangan di Desa Lampulung Kabupaten Wajo - Agus Purwanto; Asrul Jaya (Compile Journal of Society Service, 2025)
The financial literacy level among rural communities remains relatively low, leading to poor financial management and decision-making. This community service activity aimed to enhance the understanding and skills of residents in Lampulung Village, Pammana Subdistrict, Wajo Regency, in managing personal and household finances through an educational workshop. The implementation methods included material presentation, interactive discussions, financial management simulations, and evaluations using pre-test and post-test instruments. The results indicated a significant improvement in participants’ awareness and knowledge regarding financial planning, cash flow recording, debt management, saving, and basic investment strategies. This workshop proved to be effective in increasing financial literacy and is expected to encourage wiser and more independent financial behavior within households.